Theatre and Mass Culture: Pedagogical Tools for Stimulating Critical Thinking - Santana, Analola (Latin American Theatre Review, 2017)
In this essay I use the performance of De monstruos y prodigios (2001) by Mexico’s Teatro de Ciertos Habitantes as a case study on how to approach a theatrical or dramatic analysis that refers to the effects of globalization and mass culture in Latin America. Today, mass media are an obligatory reference for theatrical production, as they create a dominant discourse that helps to shape how everyday “reality” is perceived. Thus, I find this to be a useful and creative pedagogical tool in promoting critical thinking in the classroom, as it leads the student to focus on the strategies used in art to question what is perceived as reality.